Lecture ethnocritique de la plaine indochinoise durassienne : représentations symboliques d’un espace-temps de la marge - Savannah Kocevar (Itinéraires)
This article provides a chronotopic study of the Kam plain as depicted by Marguerite Duras in her Indochinese cycle (Un barrage contre le Pacifique, 1950, L'Eden cinéma, 1977, L'Amant, 1984, L'Amant de la Chine du Nord, 1991). The ethnocritical approach—a literature analysis method that combines poetry of the texts and ethnology of the symbols—shall be used in the perspective of an anthropological and symbolic interpretation of space and time, combining the notions of ritual and narration, so as to provide a proofreading of the works of Duras. According to this hypothesis, the outlines of the narrative process are assumed to be structured by the textualization of a marginal period, where the impossibility of any passage cripples the continuum of the cycle. Thus, the chronotopic analysis grid can help underline the main dynamics of the rituals staking the initiatory routes, and the acquaintances of the characters with the phase of fringe.